Visible-Light-Driven Single-Component BiVO4 Micromotors with the Autonomous Ability for Capturing Microorganisms - Villa, Katherine; Novotný, Filip; Zelenka, Jaroslav; Browne, Michelle P; Ruml, Tomáš; Pumera, Martin (ACS nano, 2019)
Light-driven micro/nanomotors represent the next generation of automotive devices that can be easily actuated and controlled by using an external light source. As the field evolves, there is a need for developing more sophisticated micromachines that can fulfill diverse tasks in complex environments. Herein, we introduce single-component BiVO4 micromotors with well-defined micro/nanostructures that can swim both individually and as collectively assembled entities under visible-light irradiation. These devices can perform cargo loading and transport of passive particles as well as living microorganisms without any surface functionalization. Interestingly, after photoactivation, the BiVO4 micromotors exhibited an ability to seek and adhere to yeast cell walls, with the possibility to control their attachment/release by switching the light on/off, respectively. Taking advantage of the selective motor/fungal cells attachment, the fungicidal activity of BiVO4 micromotors under visible illumination was also demonstrated. The presented star-shaped BiVO4 micromotors, obtained by a hydrothermal synthesis, contribute to the potential large-scale fabrication of light-powered micromotors. Moreover, these multifunctional single-component micromachines with controlled self-propulsion, collective behavior, cargo transportation, and photocatalytic activity capabilities hold promising applications in sensing, biohybrids assembly, cargo delivery, and microbiological water pollution remediation.
Keywords: fungicidal activity; povrchové vlastnosti; Particle Size; Nanostructures; micromotors; Saccharomyces cerevisiae; nanostruktury; Bismuth; Electrochemical Techniques; bismuth vanadate; světlo; elektrochemické techniky; bismut; visible light; velikost částic; Surface Properties; cargo transport; Vanadates; Light; vanadáty